ANALISIS PERBEDAAN ABNORMAL RETURN PERUSAHAAN SEKTOR ENERGI DAN PERTAMBANGAN SEBELUM DAN SETELAH PENGUMUMAN SIDANG SENGKETA PEMILU PRESIDEN 2024 - Amin, Mohammad Arridho Nur (LP2M Universitas Bina Bangsa, 2024)
Stocks are an investment instrument that still attracts many enthusiasts, both potential investors and investors who have been investing in stocks for a long time, but stocks can be affected as a result of an event, one of which is the announcement of the results of the 2024 presidential election dispute hearing. The 2024 presidential election results dispute hearing showed that energy and mining sector stocks declined around the date of the announcement of the results of the 2024 election dispute hearing. The analysis used was paired t-test samples with a window period, namely five days before the announcement, one day on the announcement date, and five days after the announcement. The results obtained were that there was no abnormal difference in returns before and after the announcement of the results of the 2024 election dispute hearing